User Satisfaction in Public Sector Digital Transformation: A Critical EUCS Analysis of the E-Kinerja Application in Indragiri Hilir Regency - Dermawan, Tri; Jazman, Muhammad; Ahsyar, Tengku Khairil; Saputra, Eki; Muttakin, Fitriani; Marsal, Arif (Jurnal Pendidikan dan Teknologi Indonesia, 2025)
The accelerated global push for digitalized public services places immense pressure on government agencies to ensure the effectiveness and user acceptance of new information systems. This study critically investigates user satisfaction with the E-Kinerja application, a pivotal e-performance management system implemented at the Regional Personnel and Human Resource Development Agency (BKPSDM) of Indragiri Hilir Regency. Utilizing the well-established End-User Computing Satisfaction (EUCS) model, encompassing content, accuracy, format, ease of use, and timeliness dimensions, this research employs a quantitative approach. Data were collected via questionnaires from 36 active users (total population) and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) in SmartPLS. The findings reveal a nuanced and unexpected pattern of influence: only the Content (T-Statistic = 2.002, p<0.05) and Timeliness (T-Statistic = 2.433, p<0.05) dimensions significantly and positively impact user satisfaction. Crucially, Accuracy, Format, and Ease of Use did not exhibit a statistically significant influence. The model explained a substantial 76.7% of user satisfaction variance. This counter-intuitive outcome challenges generalized EUCS applicability in mandatory government contexts, suggesting that user priorities in public sector performance systems may uniquely emphasize core utility and promptness over aesthetic or perceived ease. These findings offer critical insights for public administrators prioritizing IT investments and contribute to refining the theoretical understanding of EUCS dynamics in specific organizational environments. Recommendations include prioritizing content quality and timely information delivery, while re-evaluating the perceived importance of other dimensions in similar government settings.